PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT SWASTA LANCANG KUNING PEKANBARU - Ernita Sibarani; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how the influence of organizational culture and work discipline on nurse performance in Hospital Private Lancang Kuning PekanbaruThis research method is descriptive and quantitative by using program of SPSS 21, where sample used is nurse performance in Hospital Private Lancang Kuning Pekanbaru with respondents as many 86 people. For sampling technique used census method. The Data collection techniques through questionnaires and interviews.The results of ananlisis use validity test, reability test, determination test, simple linear regression test, multiple linear regression test, t test and F test so that it can be seen that motivation variables significantly influence nurse performance, that work discipline has a significant effect on nurse performance, and A significant influence between motivation and work discipline on nurse performance.Keyword: Motivation, Work Discipline, and Employee Performance